2017
DOI: 10.1016/j.bbi.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-induced anorexia and fever are elicited by distinct prostaglandin dependent mechanisms, whereas conditioned taste aversion is prostaglandin independent

Abstract: HighlightsLPS-induced anorexia depends on COX-2, but not in brain endothelial, myeloid or neural cells.LPS-induced anorexia and fever are elicited by prostaglandin synthesis in distinct cell groups.Conditioned taste aversion induced by LPS is prostaglandin-independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…Food and water were removed 4 h before injection to increase feeding drive. LPS from Escherichia coli [Sigma-Aldrich, Saint Louis, MO; O111:B4; 10 or 120 µg/kg body weight; doses based on findings in previous studies (Elander et al, 2007;Nilsson et al, 2017)] diluted in 0.1 ml saline, or saline only, was injected intraperitoneally (ip) 1 h before light-off. Food and water were returned to the cage 1 h after injection.…”
Section: Injection Of Lps or Saline And Measurement Of Food Intakementioning
confidence: 99%
“…Food and water were removed 4 h before injection to increase feeding drive. LPS from Escherichia coli [Sigma-Aldrich, Saint Louis, MO; O111:B4; 10 or 120 µg/kg body weight; doses based on findings in previous studies (Elander et al, 2007;Nilsson et al, 2017)] diluted in 0.1 ml saline, or saline only, was injected intraperitoneally (ip) 1 h before light-off. Food and water were returned to the cage 1 h after injection.…”
Section: Injection Of Lps or Saline And Measurement Of Food Intakementioning
confidence: 99%
“…Studies have suggested that mPGES1 primarily couple to COX-2 over COX1, but other findings demonstrate exceptions to this rule, and mPGES1 has been found to couple to COX1 in cases where the concentration of arachidonic acid is high (Matousek et al, 2010;Chandrasekharan et al, 2005;Murakami et al, 2000). COX2 provides the main source of prostaglandin E2 production mediating inflammatory symptoms such as fever and loss of appetite (Wilhelms et al, 2014;Nilsson et al, 2017a) and in particular endothelial mPGES1 is important for the pyrogenic response to inflammation (Ek et al, 2001;Engblom et al, 2003;Wilhelms et al, 2014). In comparison, COX 1 is responsible for PGE2 leading to social defeat stress, which has been implied to involve microglial activation (Tanaka et al, 2012), and COX-1 expression in endothelial cells has been suggested to drive the early phase of corticosterone release during systemic inflammation (Elander et al, 2009;Garcia-Bueno et al, 2009).…”
Section: Prostaglandin E2 Synthesis and Receptorsmentioning
confidence: 99%
“…from K-235 E. coli. At this dose, mice display mild symptoms of the sickness syndrome including elevated body temperature and anorexia (Nilsson et al, 2017a). Many animal models used for investigating inflammation-induced negative affective state are based on administrations of high doses of LPS (500-2500 µg/kg) (O'Conner et al, Biesmans et al, 2013).…”
Section: Models Of Systemic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many sickness behaviors such as chills and goose pimples, assuming the fetal position to reduce body surface area, or wearing thick clothing and seeking warmer environments can be observed. Systemic symptoms such as headache, somnolence, and a decrease in motor activity, as well as hypophagia (a decrease in food intake), which leads to loss of body mass, may also accompany fever [2,3]. When the fever signal is no longer present and the set point reverts back to "normal", the body temperature returns to the physiological range by activation of heat loss mechanisms such as sweating [4][5][6].…”
mentioning
confidence: 99%